PERFORMANCE EVALUATION OF IEEE 802.15.4 NETWORKS IN THE PRESENCE OF α-η-μ FADING, INTERFERENCE AND NOISE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
A novel, mathematically tractable expression for evaluation of the average chip error probability (CEP) in the networks based on IEEE802.15.4 standard, operating in the 2450 MHz band, in the presence of α-η-μ fading, interference and additive white Gaussian noise (AWGN) is presented. The expression is validated by Monte Carlo simulations and represents the foundation for performance evaluation of the mentioned type of networks operating over any type of non-line-of-sight (NLoS) channel. In addition, we have demonstrated practical usage of the derived average CEP expression by evaluating the average packet error probability (PEP) for the above-described network operating conditions.